2004
DOI: 10.1074/jbc.m310330200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Dose-dependently Prevents Palmitate-induced Apoptosis by Both Protein Kinase A- and cAMP-Guanine Nucleotide Exchange Factor-dependent Pathways in β-Cells

Abstract: Lipid accumulation in pancreatic ␤-cells is thought to cause its dysfunction and/or destruction via apoptosis. Our studies show that incubation of the ␤-cell line RINm5F with the saturated free fatty acids (FFA) palmitate caused apoptosis based on increases in caspase 3 activity, Annexin V staining, and cell death. Furthermore, exposure of RINm5F cells to cAMP-increasing agents, 3-isobutyl-1-methylxanthine (IBMX), and forskolin completely abolished palmitate-mediated caspase 3 activity and significantly inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 28 publications
7
86
0
2
Order By: Relevance
“…Also interesting was the fact that FSKmediated activation of the insulin gene was not completely inhibited by PKA inhibitors (maximum 80% inhibition) in the studies by Lawrence and co-workers. This would suggest, as has been found for other GLP-1 actions on the β cell (Kwon et al, 2004b), that PKA is a major regulator of insulin transcription when the levels of cAMP are lower and more localized. There are three putative binding sites [(T/A)GGAAA(A/N)(A/T/C) where N=nucleotide] for NFAT on RIP1 (see Fig.…”
Section: Glp-1 Regulation Of Insulin Transcriptionmentioning
confidence: 59%
See 2 more Smart Citations
“…Also interesting was the fact that FSKmediated activation of the insulin gene was not completely inhibited by PKA inhibitors (maximum 80% inhibition) in the studies by Lawrence and co-workers. This would suggest, as has been found for other GLP-1 actions on the β cell (Kwon et al, 2004b), that PKA is a major regulator of insulin transcription when the levels of cAMP are lower and more localized. There are three putative binding sites [(T/A)GGAAA(A/N)(A/T/C) where N=nucleotide] for NFAT on RIP1 (see Fig.…”
Section: Glp-1 Regulation Of Insulin Transcriptionmentioning
confidence: 59%
“…As discussed earlier in section 3.3 under conditions of low and localized subcellular increases in cAMP as in those stimulated by GLP-1R activation of AC the preferred pathway appears to be via PKA activation rather than through Epac2. Kwon and co-workers have demonstrated that this is the case for the antiapoptotic properties of GLP-1 in which they also found a PKA-dependent component of the mechanism in the prevention of FFA-induced apoptosis in RINm5F cells (Kwon et al, 2004b).…”
Section: β Cell Toxicity and Death: Protective Effects Of Glp-1r Agonmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, the anti-apoptotic action of GLP-1 has also been demonstrated in freshly isolated human islets [13]. Furthermore, GLP-1 increased the survival of immortalised rodent beta cell lines after challenge with various apoptotic stimuli [12,[14][15][16][17]. Because of these actions, GLP-1 offers several potential therapeutic advantages for patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…Recent data show that the actions of GLP-1 that protect against diabetes also include the enhancement of beta cell mass in rodents, through inhibition of beta cell apoptosis, and stimulation of beta cell proliferation and islet neogenesis [16][17][18][19]. Furthermore, GLP-1 and its agonists increase the survival of immortalised rodent beta cell lines when challenged with various apoptotic stimulators, including hydrogen peroxide, fatty acids, streptozotocin and staurosporine [17,[20][21][22]. Importantly, exendin-4 treatment also reduces cytokine-induced apoptosis in purified rat beta cells [17].…”
Section: Introductionmentioning
confidence: 99%